Associations between Maternal and Fetal Inherited Thrombophilias, Placental Characteristics Associated with Vascular Malperfusion, and Fetal Growth - Freedman, Alexa A.; Hogue, Carol J.; Dudley, Donald J.; Silver, Robert M.; Stoll, Barbara J.; Pinar, Halit; Goldenberg, Robert L.; Drews-Botsch, Carolyn (TH Open, 2017)
Pregnancy results in alterations in coagulation processes, which may increase the risk of thrombosis. Inherited thrombophilia mutations may further increase this risk, possibly through alterations in the placenta, which may result in pregnancy complications such as poor fetal growth. The purpose of our study is to evaluate the association of fetal growth, approximated by birth weight for gestational age percentile, with genetic markers of thrombophilia and placental characteristics related to vascular malperfusion. We analyzed data from the Stillbirth Collaborative Research Network's population-based case–control study conducted in 2006–2008. Study recruitment occurred in five states: Rhode Island and counties in Massachusetts, Georgia, Texas, and Utah. The analysis was restricted to singleton, nonanomalous live births ≤42 weeks' gestation with a complete placental examination and successful testing for ≥1 thrombophilia marker (858 mothers, 902 infants). Data were weighted to account for oversampling, differential consent, and availability of placental examination. We evaluated five thrombophilia markers: factor V Leiden, factor II prothrombin, methylenetetrahydrofolate reductase A1298C and C677T, and plasminogen activator inhibitor type 1 in both maternal blood and placenta/cord blood. We modeled maternal and fetal thrombophilia markers separately using linear regression. Maternal factor V Leiden mutation was associated with a 13.16-point decrease in adjusted birth weight percentile (95% confidence interval: −25.50, −0.82). Adjustment for placental abnormalities related to vascular malperfusion did not affect the observed association. No other maternal or fetal thrombophilia markers were significantly associated with birth weight percentile. Maternal factor V Leiden may be associated with fetal growth independent of placental characteristics.
Keywords: pregnancy; inherited thrombophilias; perinatal hemostasis